Women's knowledge and attitudes surrounding abortion in Zambia: a cross-sectional survey across three provinces. Issue 3 (21st March 2016) - Cresswell, Jenny A; Schroeder, Rosalyn; Dennis, Mardieh; Owolabi, Onikepe; Vwalika, Bellington; Musheke, Maurice; Campbell, Oona; Filippi, Veronique
Abstract : Objectives: In Zambia, despite a relatively liberal legal framework, there remains a substantial burden of unsafe abortion. Many women do not use skilled providers in a well-equipped setting, even where these are available. The aim of this study was to describe women's knowledge of the law relating to abortion and attitudes towards abortion in Zambia. Setting: Community-based survey in Central, Copperbelt and Lusaka provinces. Participants: 1484 women of reproductive age (15–44 years). Primary and secondary outcome measures: Correct knowledge of the legal grounds for abortion, attitudes towards abortion services and the previous abortions of friends, family or other confidants. Descriptive statistics and multivariable logistic regression were used to analyse how knowledge and attitudes varied according to sociodemographic characteristics. Results: Overall, just 16% (95% CI 11% to 21%) of women of reproductive age correctly identified the grounds for which abortion is legal. Only 40% (95% CI 32% to 45% of women of reproductive age knew that abortion was legally permitted in the extreme situation where the pregnancy threatens the life of the mother. Even in urban areas of Lusaka province, only 55% (95% CI 41% to 67%) of women knew that an abortion could legally take place to save the mother's life. Attitudes remain conservative. Women with correct knowledge of abortion law in Zambia tended to have more liberal attitudes towards abortion and access to safe abortion services. Neither correct knowledge of the law nor attitudes towards abortion were associated with knowing someone who previously had an induced abortion. Conclusions: Poor knowledge and conservative attitudes are important obstacles to accessing safe abortion services. Changing knowledge and attitudes can be challenging for policymakers and public health practitioners alike. Zambia could draw on its previous experience in dealing with its large HIV epidemic to learn cross-cutting lessons in effective mass communication on what is a difficult and sensitive issue.